Association of congenital heart disease and neurodevelopmental disorders: an observational and Mendelian randomization study - Zhi-yuan Liu; Qiong-qiong Wang; Xian-yong Pang; Xiao-bi Huang; Gui-ming Yang; Sheng Zhao (BMC, 2024)
Abstract Background This study aims to thoroughly study the connection between congenital heart disease (CHD) and neurodevelopmental disorders (NDDs) through observational and Mendelian randomization (MR) designs. Methods This observational study uses data from the National Survey of Children's Health (2020-2021). Multivariable logistic regression and propensity score matching (PSM) were performed to analyze the association. PSM was used to minimize bias for covariates such as age, race, gender, maternal age, birth weight, concussion or brain injury, preterm birth, cerebral palsy, Down syndrome, and other inherited conditions. In MR analyses, inverse variance-weighted measures, weighted median, and MR-Egger were employed to calculate causal effects. Results A total of 85,314 children aged 0-17 were analyzed in this study. In regression analysis, CHD (p = 0.04), the current heart condition (p = 0.03), and the severity of current heart condition (p < 0.05) had a suggestive association with speech or language disorders. The severity of current heart condition (p = 0.08) has a potential statistically significant association with attention deficit hyperactivity disorder(ADHD). In PSM samples, ADHD(p = 0.003), intellectual disability(p = 0.012), and speech or language disorders(p < 0.001) were all significantly associated with CHD. The severity of current heart condition (p < 0.001) also had a significant association with autism. MR analysis did not find causality between genetically proxied congenital cardiac malformations and the risk of NDDs. Conclusions Our study shows that children with CHD have an increased risk of developing NDDs. Heart conditions currently and severity of current heart conditions were also significantly associated with these NDDs. In the future, we need to try more methods to clarify the causal relationship between CHD and NDDs.